Determination of the hidraulic conductivity in a Red-Yellow Podzolic under field conditions - Junior, Thomaz Corrêa Aragão; Magalhães, Carlos Alberto de; Castro, Paulo Teodoro de (Pesquisa Agropecuaria Brasileira, 2014)
This hidraulic conductivity at two depths was studied with the objective of determining the flux of internal drainage in a Red-YeIIow Podzolic latosol, using the instantaneous profile method. The values of hidraulic conductivity at the two dephts are descripted by the equations: K22,5 = exp 27,2 (3,34470-1) cm and K37,5 exp 26,8 (4,16640-1) cm.